2013
DOI: 10.1136/annrheumdis-2013-203565
|View full text |Cite
|
Sign up to set email alerts
|

Anti-citrullinated protein antibodies acquire a pro-inflammatory Fc glycosylation phenotype prior to the onset of rheumatoid arthritis

Abstract: ObjectiveTo determine whether anticitrullinated protein antibodies (ACPA) exhibit specific changes in Fc glycosylation prior to the onset of arthritis.MethodsSerum samples of patients with ACPA-positive arthralgia (n=183) were collected at baseline and at various time points of follow-up. 105 patients developed arthritis after a median of 12 months (IQR 6–24) and were classified as having either rheumatoid arthritis (RA, n=48) or undifferentiated arthritis (UA, n=57) based on the 1987 American College of Rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
161
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 235 publications
(182 citation statements)
references
References 52 publications
16
161
2
3
Order By: Relevance
“…Earlier, we and others reported that the galactosylation and sialylation levels of Fc-glycans from ACPA-IgG is lower compared with control IgG, and this is more pronounced in ACPA-IgG isolated from SF (28,29). In addition, we observed that the changes of ACPA-IgG Fcglycosylation already occur a few months before of the diagnosis of RA (23).…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wesupporting
confidence: 55%
See 4 more Smart Citations
“…Earlier, we and others reported that the galactosylation and sialylation levels of Fc-glycans from ACPA-IgG is lower compared with control IgG, and this is more pronounced in ACPA-IgG isolated from SF (28,29). In addition, we observed that the changes of ACPA-IgG Fcglycosylation already occur a few months before of the diagnosis of RA (23).…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wesupporting
confidence: 55%
“…As expected, control IgG was characterized by two electrophoretic bands corresponding to the heavy and light chains (HC and LC), whereas ACPA-IgG showed several HC and LC bands with higher molecular weights as described previously (13). Released N-glycans from both the HC of IgG and the HC1 of ACPA-IgG displayed a typical Fc-linked glycan profile in UHPLC (23,26), whereas no N-glycans were detected in the LC of IgG and the LC1 of ACPA-IgG (Fig. 2B).…”
Section: Quantification Of the N-glycans Expressed By Igg Andmentioning
confidence: 89%
See 3 more Smart Citations